Developing a strategic sustainable facility plan for a hospital layout using ELECTRE and Apples procedure - K.E.K, Vimal; Kandasamy, Jayakrishna; Nadeem, Simon Peter; Kumar, Anil; Šaparauskas, Jonas; Garza-Reyes, Jose Arturo; Trinkūnienė, Eva (International Journal of Strategic Property Management, 2021)
Today healthcare globally is growing at a rapid pace and despite the huge technological advancement, healthcare still faces primitive challenges and hence results in the poor service and facility to the needy. Layout planning acts as one major reason which requires improvements for the effective and efficient working of the healthcare facilities. This research aims at optimizing several quantitative criteria related to economic, technology and society which are taken into consideration for the decision-making during the evaluation, analysing and selection of the best layout for an existing healthcare facility. Critical areas for the improvement were found out using statistical analysis based on a survey questionnaire and Apple’s layout procedure is utilised to design the different possible layouts for an efficient facility. The seven criteria namely inter-departmental satisfactory level, the average distance travelled and the average time required for staff flow, the average distance travelled and the average time required for patient flow, the average distance travelled and the average time required for material flow were taken into consideration. The ELECTRE methodology was used as multi-criteria decision making based on decided seven criteria for comparing the different layout by methodical and orderly thinking. First published online 23 November 2020